EFFICACY OF TOPICAL CLOTRIMAZOLE IN TREATMENT OF OTOMYCOSIS - Khan, Farida; Muhammad, Raza; Khan, Muhammad Riaz; Rehman, Fazal; Iqbal, Johar; Khan, Munib; Ullah, Gohar (Journal of Ayub Medical College Abbottabad, 2013)
Background: Otomycosis is a common condition affecting external ear and ears with chronic suppurative otitis media, and has a tendency for recurrence. Objective of this study was to determine the efficacy of topical clotrimazole in the treatment of otomycosis. Methods: This descriptive study was conducted at the outpatient department of ENT, Ayub Teaching Hospital Abbottabad, from Jul 2012 to Dec 2012. A total of 101 patients were included in this study. The results were compared and analysed regarding age, gender, presenting complaints and efficacy of clotrimazole. Results: A total of 101 patients of otomycosis were included in the study. Male to female ratio was 0.71:1. Patients of 15 years and above were included in the study. Adults were more affected by otomycosis than the younger age group. The efficacy of clotrimazole in treatment of otomycosis was observed in 89 (94.12%) while in 12 (5.88%) patients no efficacy was seen. Age and gender have no role in efficacy of Clotrimazole in treatment of Otomycosis. Conclusion: Topical clotrimazole is effective in the treatment of Otomycosis. Keywords: Otomycosis, Clotrimazole